2014
DOI: 10.1007/s10761-014-0264-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Stable Isotope and Zooarchaeological Analyses in Historical Archaeology: A Case Study from the Urban Nineteenth-Century Commonwealth Block Site, Melbourne, Australia

Abstract: This paper presents the first use of bone collagen stable isotope analyses for the purpose of reconstructing historical animal husbandry and trade practices in Australia. Stable carbon and nitrogen isotope analyses of 51 domesticate and commensal specimens demonstrate that meats consumed at the mid to late nineteenth-century Commonwealth Block site in Melbourne derived from animals with a diverse range of isotopic signatures. Potential factors contributing to this diversity including animal trade and variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…Isotopic analyses of archaeological rat bones can be used to reconstruct patterns in what foods were available to rats in human settlements through time [ 12 ] and across space [ 13 ]. In addition to providing a baseline for the kinds of food that rats scavenged [ 14 ], these data also provide details on how broader cultural (socio-economic shifts related to food production) [ 12 , 15 ] and environmental (impacts on landscapes and native taxa) [ 13 ] processes unfold. Moreover, isotopic analyses of archaeological rat remains may be used to reveal patterns in where and how rats have been most successful at exploiting human settlements.…”
Section: Introductionmentioning
confidence: 99%
“…Isotopic analyses of archaeological rat bones can be used to reconstruct patterns in what foods were available to rats in human settlements through time [ 12 ] and across space [ 13 ]. In addition to providing a baseline for the kinds of food that rats scavenged [ 14 ], these data also provide details on how broader cultural (socio-economic shifts related to food production) [ 12 , 15 ] and environmental (impacts on landscapes and native taxa) [ 13 ] processes unfold. Moreover, isotopic analyses of archaeological rat remains may be used to reveal patterns in where and how rats have been most successful at exploiting human settlements.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest the individual recovered in the burial did not have a diet that was atypical of 19 th ‐century dogs living in urban areas based on comparisons with the other dog specimen from this site, to others from urban sites (e.g. Guiry et al ., ) and to early results of ongoing work in southern Ontario by one of this paper's co‐authors (Guiry). Moreover, isotopic values from early and late forming tissues are similar suggesting that this individual's diet was (in terms of stable isotopes) consistent throughout his life.…”
Section: Resultsmentioning
confidence: 88%
“…Medieval domesticate δ 15 N from sites across Ireland (15 sites, herbivore n=100, 6.3 ± 1.2‰; 15 sites, omnivore n=79, 7.9 ± 1.9‰ (Guiry, et al, 2018a) are close to those observed at Ballyhanna (herbivore n=10, 6.3 ± 0.8‰; omnivore n=1, 7.2‰) suggesting that these data reflect typical values for the time period. It is also worth bearing in mind that substantial intra-site variability in δ 15 N (up to c. 5‰) in both herbivores and omnivores is evident across many Irish Medieval sites (Guiry, et al, 2018a), a pattern that is common across historical archaeological sites around the world (Guiry, et al, 2017, Guiry, et al, 2014, Guiry, et al, 2018b, Reitsema, et al, 2015, Guiry, et al, 2012, Guiry, et al, 2015. The extreme degree of isotopic variation in Medieval Irish fauna likely reflects a high level of heterogeneity in both animal husbandry and local nitrogen cycling at relatively small spatial and temporal scales.…”
Section: Stable Isotopesmentioning
confidence: 99%